Peran Penting Bank Syariah Digital Dalam Menghadapi Isu-Isu Keuangan Publik - Koesherawati, Andini Ashra; Oktari, Vivi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The presence and application of Islamic banks in Indonesia have been going on for almost three decades, but the development of its business has not been in accordance with the duration that has been passed. At the end of 2016, the growth of Islamic banks reached 19.67 percent with a market share of 5.12 percent. This figure shows an imbalance with the great potential possessed by Indonesia. Several inhibiting factors include limited Islamic products and services, distance to bank locations, high costs for small-volume transactions, limited information, low levels of Islamic financial literacy and inclusion, and long queues in direct transactions. This research was conducted through literature studies and field observations. To analyze the data, three analysis methods were used, namely inductive, deductive, and comparative methods. The inductive method is used to find facts based on specific reasons in order to produce general conclusions. The results of the analysis show low levels of Islamic financial literacy and inclusion, at 8.11 percent and 11.06 percent, respectively. Therefore, innovation is needed to overcome service gaps, one of which is by utilizing information and communication technology through service digitization. Digitization is expected to bring closer relations between Islamic banks and the community in a more efficient, economical, fast and economical way.